Penggunaan Artifical Inteligence (AI) Dalam Penelitian Pendidikan IPA Dari Sisi Etika Keilmuwan: Systematic Literature Review - Dzulkifli Nurul Huda; Safina Aulia Sani; Firma Nur Muttaqin; Dyah Ismi Safitri; Suratno Suratno; I Ketut Mahardika (Peneliti.net, 2026)
This research study investigates the utilisation of Artificial Intelligence (AI) in scientific research and learning from an educational science ethics perspective. The methodology employed is a systematic literature review (SLR) with analysis of various theoretical sources related to the application of AI. The findings of the study demonstrate that AI has the capacity to expedite substantial data processing, discern latent patterns, and fortify scientific reasoning. In the context of education, AI chatbots such as ChatGPT and Gemini have been shown to facilitate critical thinking skills, dispel misconceptions, and encourage independent learning. The utilisation of AI is obligated to adhere to a set of ethical principles, encompassing privacy, fairness, transparency, human oversight, and accessibility. Additionally, measures must be implemented to mitigate bias, thereby ensuring the validity of research outcomes. Responsible AI guidelines emphasise the use of AI as an ethical and responsible tool, with researchers retaining control over scientific interpretation and conclusions. This study underscores the significance of incorporating scientific ethics into the implementation of AI in science education.